Penetapan Mahkamah Agung atas Permohonan Perkawinan Beda Agama Perspektif Teori Hukum Progresif - Naim, Amal Zainun (Al-Faruq: Jurnal Hukum Ekonomi Syariah dan Hukum Islam, 2024)
This article aims to review the Supreme Court (MA) decisions in 1986 and 2017 regarding requests for interfaith marriages from the perspective of progressive legal. Law of the Republic of Indonesia no. 1 of 1974 concerning indecisive marriages in regulating interfaith marriages, this has become one of the factors in the number of submissions of interfaith marriages to the District Court. Heterogeneous Indonesian society and the influence of the globalization era have made the increasing submission of interfaith marriages in Indonesia. This study is a normative study and data obtained from copies of Supreme Court decisions and books and scientific articles related to the topic of discussion. The results showed that the 1986 MA ruling considered philosophical, sociological and juridical aspects and the 2017 MA ruling considered juridical aspects.